2023
DOI: 10.1002/advs.202207334
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Adipose‐Derived Stem Cells for Regenerative Medicine: Where Challenge Meets Opportunity

Abstract: Over the last decade, adipose‐derived stem cells (ADSCs) have attracted increasing attention in the field of regenerative medicine. ADSCs appear to be the most advantageous cell type for regenerative therapies owing to their easy accessibility, multipotency, and active paracrine activity. This review highlights current challenges in translating ADSC‐based therapies into clinical settings and discusses novel strategies to overcome the limitations of ADSCs. To further establish ADSC‐based therapies as an emergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 252 publications
0
14
0
Order By: Relevance
“…ADSCs can differentiate in vitro and in vivo into osteogenic, chondrogenic, myogenic, epithelial, endothelial, and neuron-like cells in the presence of lineage-specific induction factors [ 31 ]. In addition, mechanical or electromagnetic stimulation, pharmaceuticals, and genetic reprogramming have been widely explored to promote the differentiation of ADSCs into specific cell lineages [ 32 , 33 ].…”
Section: Adsc Characteristicsmentioning
confidence: 99%
“…ADSCs can differentiate in vitro and in vivo into osteogenic, chondrogenic, myogenic, epithelial, endothelial, and neuron-like cells in the presence of lineage-specific induction factors [ 31 ]. In addition, mechanical or electromagnetic stimulation, pharmaceuticals, and genetic reprogramming have been widely explored to promote the differentiation of ADSCs into specific cell lineages [ 32 , 33 ].…”
Section: Adsc Characteristicsmentioning
confidence: 99%
“…Regenerative medicine is a treatment modality that restores function by regenerating tissues and organs lost due to accident or disease, and cell transplantation treatment using stem cells is a known form of this modality [ 35 ]. However, regenerative medicine requires a special cell culture facility, leading to higher medical costs, the risk of mutations occurring during cell culture, and slow supply speeds based on the time required for culture [ 36 , 37 , 38 ]. “Stem cells” is a general term for cells that have both self-renewal ability and multipotency and include somatic stem cells (adult stem cells, tissue stem cells), embryonic stem (ES) cells, induced pluripotent stem cells (iPSCs), etc.…”
Section: Mrna-based Protein Supplementation For Regenerative Medicinementioning
confidence: 99%
“…Adipose-derived stem cells (ADSCs) are commonly applied in the reconstruction and repair of soft tissues, playing a pivotal role in both plastic surgery and tissue engineering ( Dai et al, 2016 ; Wankhade et al, 2016 ; Gadelkarim et al, 2018 ). Numerous studies have demonstrated that during in vitro cultivation, ADSCs could secret a multitude of bioactive cytokines and growth factors, including transforming growth factor-β, hepatocyte growth factor (HGF) and vascular endothelial growth factor (VEGF) ( Qin et al, 2023 ; Wang et al, 2023 ; Wu et al, 2023 ). These mediators are instrumental in fostering cell proliferation, cellular migration, angiogenesis regulation, immune response modulation, and inflammation response regulation, assuming an indispensable role in the wound repair process ( Song Y. et al, 2023 ; Wu et al, 2023 ; Kang et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%